Tsongkhapa: a Buddha in the land of snows - Thub-bstan-sbyin-pa (Lives of the Masters, 2019)
Birth and early years -- Education in central Tibet -- Coming of age -- Queries from a sincere heart -- The mystery of Guru Mañjuśri -- Intensive retreat in the Wölkha Valley -- The Lhodrak mystic : one more piece of the puzzle -- Finally, the breakthrough! -- The two great syntheses -- Hermeneutics and philosophical analysis -- Lhasa prayer festival and the founding of Ganden -- Yogi of glorious Guhyasamāja -- Yogi of Cakrasaṃvara tantra -- Last few months and nirvāṇa -- Canonization and the consolidation of the master's legacy.